Experimental and numerical studies on current distribution in stacks of HTS tapes for cable-in-conduit-conductors. (2nd February 2021) - De Marzi, Gianluca; Celentano, Giuseppe; Augieri, Andrea; Marchetti, Marcello; Vannozzi, Angelo
Abstract: Cable-in-conduit conductors comprised of twisted stacks of high-temperature superconducting (HTS) tapes constitute a very promising technology by virtue of their easy manufacturing process, flexibility capabilities, and high current densities. In a cable, the current distribution among tapes is one of the key parameters affecting the cable performances. The distribution of current is affected mainly by the self-field configuration (ultimately related to the cable layout) and the termination resistances. In this paper we present a 2D finite element (FE) model, based on the T-A formulation, which computes the magnetic field and current distribution in stacked tapes. This model has been used to describe the experimental V–I results obtained in cables in which different current distributions among tapes are expected. The first case refers to V–I curves of stacks of HTS tapes inserted into ducts formed in the extruded aluminium cylindrical core for a straight cable. The excellent agreement between the experimental findings and the simulation results can be explained in terms of uniform current distribution within the tapes stack, up to the superconducting to normal transition. The second sample, an Al-slotted core Cable-In-Conduit-Conductor, has been bent down to a radius of 0.15 m, and from the measured V–I characteristic of each individual tape, a different tape degradation depending on the tape position within the stack was recorded. The model is able to reconstruct the V–I of the stacks from the characteristic curves of the individual tapes with a satisfactory agreement. The finite element analysis reveals non-uniform current distribution among the tapes, which could expose the cable to a potentially irreversible damage during operation. The proposed FE model constitutes a useful tool for the analysis and predictions of HTS CIC conductor performances and represents a suitable basis for the implementation of more complex models aimed at the design of specific and large applications of this conductor in the next future.